PEMBUATAN ASAP CAIR DARI LIMBAH TONGKOL JAGUNG DENGAN METODE PIROLISIS YANG DIGUNAKAN SEBAGAI PENGAWET PADA IKAN - Erna Frida; Darnianti Darnianti; Noviyunida Noviyunida (Universitas Quality, 2018)
Corncob is one of the organic waste which so far still not used as a product that has added value. It turns out that corn cobs can be utilized into liquid smoke which is useful for environmentally friendly food preservatives. In this research, the raw material used is corncob waste as liquid smoke manufacture. The method used is pyrolysis method using pyrolysis reactor, by burning and heating on the furnace which will produce smoke and then it will be condensed (water vapor in the air condenses from gas form, back to liquid) into liquid smoke or liquid smoke. The result of rendeman characterization is 4.3-5%, liquid smoke pH 2.8-3.0 and liquid smoke test applied to mujair fish can survive for 20 days.